A white-collar profession : African American certified public accountants since 1921 - Hammond, Theresa A. (University of North Carolina Press, 2002)
This publication provides a history of black exclusion from accounting and the pioneering efforts of the first black CPAs. It chronicles the determination of African Americans who sought to enter the field and gives a broad understanding of links between race, education and economics.